Downregulating VAC14 in Guard Cells Causes Drought Hypersensitivity by Inhibiting Stomatal Closure - Wang, Zong-Qi; Liu, Qi; Wu, Ju-Hua; Li, Juan; He, Jun-Min; Zhang, Yan; Li, Sha (Frontiers in Plant Science, 2020)
The formation of stomata is a key invention of terrestrial plants to adapt to environment. Stomatal movement determines water transpiration, the efficiency of photobiosynthesis, as well as plant responses to stresses. Stomatal movement is controlled by various environmental and physiological factors and associates with multiple intracellular activities, among which the dynamic remodeling of vacuoles plays a crucial role. Phosphatidylinositol 3,5-bisphosphate [PI(3,5)P2] is critical for dynamic remodeling of vacuoles. Its production requires a PI(3,5)P2-metabolising complex consisting of FAB1/PIKfyve kinases, SAC phosphatases, and the scaffolding protein VAC14. Although genetic or pharmacologic downregulation of PI(3,5)P2 causes hyposensitivity to ABA-induced stomatal closure, whether the effect of PI(3,5)P2 on stomatal movement is cell-autonomous and the physiological consequences of its reduction were unclear. We report that downregulating Arabidopsis VAC14 specifically in guard cells by artificial microRNAs (amiR-VAC14) results in enlarged guard cells and hyposensitivity to ABA- and dark-induced stomatal closure. Vacuolar fission during stomatal closure is compromised by downregulating VAC14 in guard cells. Exogenous PI(3,5)P2 rescued whereas its inhibitor YM201636 mimicked the hyposensitivity of amiR-VAC14 plants toward ABA. We further show that downregulating VAC14 specifically in guard cells impairs drought tolerance, suggesting a key role of guard cell-produced PI(3,5)P2 in plant fitness.